2016
DOI: 10.1016/j.neulet.2016.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of force-field adaptation in proprioceptively-deafferented subjects

Abstract: Humans have the remarkable ability to adapt their motor behaviour to changes in body properties and/or environmental conditions, based on sensory feedback such as vision and proprioception. The role of proprioception has been highlighted for the adaptation to new upper-limb dynamics, which is known to generalize to the opposite, non-adapted limb in healthy individuals. Such interlimb transfer seems to depend on sensory feedback, and the present study assessed whether the chronic loss of proprioception preclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…They also showed that training reshaped the profile of this variability across different tasks, implying its active regulation (see also Pekny et al 2015). Wong and Shelhamer (2014) reported similar relationships between baseline errors and adaptation of saccadic eye movements, while Lefumat et al (2015) showed that variability of arm movement during the adaptation phase was correlated with the amount of inter-manual transfer of force-field adaptation, a finding that also held up for two participants with PL (Lefumat et al 2016). …”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…They also showed that training reshaped the profile of this variability across different tasks, implying its active regulation (see also Pekny et al 2015). Wong and Shelhamer (2014) reported similar relationships between baseline errors and adaptation of saccadic eye movements, while Lefumat et al (2015) showed that variability of arm movement during the adaptation phase was correlated with the amount of inter-manual transfer of force-field adaptation, a finding that also held up for two participants with PL (Lefumat et al 2016). …”
Section: Introductionmentioning
confidence: 89%
“…IW (male, 61 years old at time of participation, 100% left-handed according to the 10-item version of the Edinburgh inventory, Oldfield 1971) has no tactile, muscle or joint proprioceptive sensation from below the collar (C3) following a selective peripheral neuronopathy brought about by a viral infection at age 19 years. GL (female, 66 years old at time of participation, right-handed with a lateral quotient of 77%; Lefumat et al 2016) suffered a similar neuronopathy except the loss of sensation is from the mouth down (trigeminal V3, Forget and Lamarre 1987; Cole and Paillard 1995). IW has apparently normal afferent sensations from neck muscles whilst GL has no afferent information from neck muscles or lower face.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations